ANALISIS PERANAN PEMERINTAH DAERAH TERHADAP PEMBERDAYAAN MASYARAKAT KABUPATEN SIDENRENG RAPPANG (Studi Kasus Pengentasan Anak Putus Sekolah di Kecamatan Maritengngae) - Siti Hardianti Arkian Siti Arkian; Saha Sahar; Andi Feby Febriani (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2020)
Abstract This writing aims to determine the effect of the role of local government on community empowerment in alleviating school dropouts in the Maritengngae District, Sidenreng Rappang Regency and to determine community empowerment in alleviating school dropouts in the Maritengngae District, Sidenreng Rappang Regency. The population in this case is 65 people, while the data collection techniques used are questionnaires, documentation, observation, while the data analysis technique used is data analysis with a frequency table. The result in writing this journal is the preparation of facilities and infrastructure for the implementation of learning (school building) is 95% in the category Strongly Agree, Operational costs allocated in the implementation of education are 73.5% with the category Strongly Agree, Empowerment of Human Resources, namely Educators in the implementation of learning is 77.25% which means the category Agree, Providing assistance in the form of Free Education for those who are unable to access Formal Education is 88 , 5% which means the category agrees, the 12 year compulsory education program to improve and develop human resources in the education sector is 66.25% which means the category Agree, alleviating school dropouts is access to underprivileged children is 74.5% which means the category Agree, the government's effort to increase HR is 74.5% which means the category agrees. Keywords: supervision and work discipline